Aldehyde dehydrogenase in regulatory T‐cell development, immunity and cancer. Issue 1 (22nd November 2018) - Bazewicz, Christopher G.; Dinavahi, Saketh S.; Schell, Todd D.; Robertson, Gavin P.
Summary: The role of aldehyde dehydrogenase (ALDH) in carcinogenesis and resistance to cancer therapies is well known. Mounting evidence also suggests a potentially important role for ALDH in the induction and function of regulatory T (Treg) cells. Treg cells are important cells of the immune system involved in promoting immune tolerance and preventing aberrant immune responses to beneficial or non‐harmful antigens. However, Treg cells also impair tumor immunity, leading to the progression of various carcinomas. ALDH expression and the subsequent production of retinoic acid by numerous cells, including dendritic cells, macrophages, eosinophils and epithelial cells, seems important in Treg induction and function in multiple organ systems. This is particularly evident in the gastrointestinal tract, pulmonary tract and skin, which are exposed to a myriad of environmental antigens and represent interfaces between the human body and the outside world. Expression of ALDH in Treg cells themselves may also be involved in the proliferation of these cells and resistance to certain cytotoxic therapies. Hence, inhibition of ALDH expression may be useful to treat cancer. Besides the direct effect of ALDH inhibition on carcinogenesis and resistance to cancer therapies, inhibition of ALDH could potentially augment the immune response to tumor antigens by inhibiting Treg induction, function and ability to promote immune tolerance to tumor cells in multiple cancer types. Abstract : Aldehyde dehydrogenase appears to be important in regulatory T‐cell development and resistance to cytotoxic therapies. Regulatory T cells promote immune tolerance but impair tumor immunity. Inhibition of ALDH may therefore modulate the immune system in ways that ultimately increase tumor immunity.